Recent Advances on Glioblastoma Multiforme and Nano-drug Carriers: A Review - Liao, Wang; Fan, Shengnuo; Zheng, Yuqiu; Liao, Shaowei; Xiong, Ying; Li, Yi; Liu, Jun (Current Medicinal Chemistry, 2019)
Glioblastoma Multiforme (GBM) is the most frequent glioma with a poor prognosis. The mainstay treatment for GBM is chemotherapy, but the average survival of GBM remains unsatisfactory due to therapeutic resistance. Poor permeability restricted by the Blood Brain Barrier (BBB) and the presence of Glioblastoma Stem Cells (GSCs) remain as two problems for chemotherapy. Recently, nanocarriers have attracted much attention in the research of GBM, owing to their advantages in self-assembly, biosafety, release controllability, and BBB penetrability, making them promising candidates for GBM treatment. This article aims to review the biologic signatures of BBB and GSCs, as well as the new development of nano-drug delivery systems to facilitate our understanding of targeted treatment for GBM.
Keywords: targeted therapy